The impact of buildup proposed barrage on tidal hydrodynamics in the Shatt Al-Arab ‎River, South of Iraq - Abdullah, ‎ Sadiq S.; Al-Fartousi‎, Adel J.; Lafta‎, Ali Ab. (Mesopotamian Journal of Marine Sciences, 2023)
The influence of the suggested regulator barrage of the Shatt Al-Arab river on water level ‎fluctuations was tested by using a one-dimensional model. The numerical model period ‎covered six months in 2017. The performance of the model was evaluated by comparing ‎the estimated water level at two locations, Sihan, and Abu Flous. A good fit between the ‎observed and simulated water levels at the two locations was achieved with root mean ‎square error at 0.13 and 0.06 m, respectively. The model results showed that there is an ‎increase in high water levels near areas located below the barrage in both the spring and ‎neap tidal phases. The increasing of water level below the barrage could be attributed to ‎behave the river as a convergent tidal channel that characterizes by the increasing water ‎level as tidal wave propagated further toward inland areas. The highest increase in the ‎water level reaches about 0.4 m below the barrage. Additionally, the tidal range also ‎increased along the river course. The maximum increase in tidal range reaches about 0.9 m ‎below the barrage. The results obtained could be useful for a general assessment of the ‎hydrodynamic of the Shatt Al- Arab river and could give a general view in the case of the ‎construction of such a barrage to tackle the salinity intrusion problem in this river.